Principles of macroeconomics - Case, Karl E.; Fair, Ray C.; Oster, Sharon M. ([Upper Saddle River, NJ] : Pearson, 2019)
"Our goal in the 13th edition, as it was in the first edition, is to instill in students a fascination with both the functioning of the economy and the power and breadth of economics. The first line of every edition of our book has been "The study of economics should begin with a sense of wonder." We hope that readers come away from our book with a basic understanding of how market economies function, an appreciation for the things they do well, and a sense of the things they do poorly. We also hope that readers begin to learn the art and science of economic thinking and begin to look at some policy and even personal decisions in a different way"--
Includes index.
Keywords: Macroeconomics